A segunda vida da Praia dos Espanhóis: dançarinos, pescadores e turistas no sul de Portugal - Pires, Ema (2017)
Abstract: In this text, we deal with proccesses of appropriation of space in the Dam of Póvoa (Portugal) using a dwelling perspective (Ingold 2009) over the territory. The reconversion of innactive spaces in rural areas into leisure-related ones in a quite common practice in contemporary times.The Spaniards beach is one of the local names given by locals to the Dam of Póvoa (Castelo de Vide), in northern Alentejo (Portugal). In the collective memory of the residents, the Dam (built in the 1920’s) is remembered for the many flowers surrounding the area. This Garden-style aesthetics has outlived the initial function of the Dam (to produce electric power). From the 1960’s to the 1980’s, it was also a popular leisure space for Spanish and Portuguese people. It is not a beach, but being inland, it was the closest thing to a beach the residents had. The centrality of this leisure space in the area only decayed after the construction of swimming pools in the nearby towns. Early in the begginning of 21st century a fire destroyed part of the natural floral landscape of the dam. Abandoned for some years, the place has still been appropriated by leisured people in day-trips (for sight-seeing, pic-nics), fishing competitions, caravan soujorns, and, since 2013, in a music and dance festival named Andanças (www.andancas.net). The research that underlies this paper was carried out between 2013 and 2016 by a team of anthropologists. An ethnography of the Dam and its uses, and of the festival and its participants was carried out. In our working-paper we higlight the main research findings achieved. Key-words: Leisure; Landscape; Tourism; Music; Space; Portugal.